The Political Economy of International Tax Governance - Rixen, T. author. aut Link
XIII, 249 p.
Keywords: Covering the period from the 1920s, when international tax policy was solely about avoiding double taxation, to the present era of international tax competition, Rixen investigates the fate of 'the power to tax' in an era of globalization, illustrating that tax sovereignty is both shaped and constrained by an international tax regime.